Enhancing Community-Based Rehabilitation for Stroke Survivors: Creating a Discharge Link. Issue 6 (November 2014) - Langstaff, Caryn; Martin, Cally; Brown, Gwen; McGuinness, Don; Mather, Jo; Loshaw, Jennifer; Jones, Nancy; Fletcher, Kim; Paterson, John
Abstract : Background and Objective: Intensive poststroke rehabilitation is critical to maximizing outcomes, improving inpatient flow, and decreasing long-term costs. This regional initiative investigated the impact of improving access to timely intensive home-based stroke rehabilitation follow-up care on hospital length of stay (LOS) and readmission rates. The enhanced service was made available across the region's rural geography to new stroke survivors transitioning home who were unable to access outpatient care.Methods: All new stroke survivors with ongoing rehabilitation needs being discharged from the hospital and eligible for home care received timely enhanced intensity of home-based rehabilitation services from existing community rehabilitation providers for 2 months after discharge. Five hundred twenty-four stroke survivors received this service over a 3-year period. The service priority rating was increased to reduce wait times to less than 5 days. Collaborative planning across sectors occurred through discharge link meetings. Comparative analysis was used to investigate health system measures before and after service implementation.Results: A 15.7-day decrease in hospital LOS and decreased hospital readmission rates were observed after enhanced service implementation. Functional Independence Measure (FIM) efficiency improved for those discharged from inpatient rehabilitation. Average wait time for community rehabilitation services decreased from 44 days to 4.4 days. The mean total number of community therapy visits more than doubled to an average of 12 per client.Conclusion: The provision of timely more intensive home-based rehabilitation services for new stroke survivors transitioning home and unable to access outpatient care was associated with decreased hospital LOS and decreased readmission rates.